2012
DOI: 10.1007/s12070-011-0347-y
|View full text |Cite
|
Sign up to set email alerts
|

Oral Dermatological Conditions: A Clinical Study

Abstract: Oral cavity consists of a small vestibule and a larger oral cavity proper. A wide number of dermatological conditions can affect the oral cavity. The clinical characteristics of the same were studied in patients attending departments of Dermatology/ENT Himalayan Institute of Medical Sciences, Dehradun. To delineate and identify the various patterns of oral dermatological conditions in this part of the country. One hundred and fifty patients were included in the study having oral lesions irrespective of age, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 14 publications
(12 reference statements)
8
18
0
Order By: Relevance
“…The current study supported evidence from similar reports Suliman et al. (2011) and Roy and Varshney (2013) that pemphigus was the most common reported MCD, and the estimated frequency in this study for pemphigus was 47.3%. However, this finding is contrary to other studies Holsen and Johannessen (2006), Rameshkumar et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study supported evidence from similar reports Suliman et al. (2011) and Roy and Varshney (2013) that pemphigus was the most common reported MCD, and the estimated frequency in this study for pemphigus was 47.3%. However, this finding is contrary to other studies Holsen and Johannessen (2006), Rameshkumar et al.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with literature (Gonçalves et al, 2010; Roy & Varshney, 2013), the current study indicated that females were more affected than males with a ratio of [2:1]; similarly, other studies (Amen et al., 2015; Babu et al., 2015; Cury et al, 2014) showed female predilection but not the same ratio.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The oral cavity is a mirror reflecting the existing illness of different human body parts. A wide number of dermatological conditions can be manifested orally [1]. Dermatoses have frequently been reported with different frequencies in the oral cavity [1].…”
Section: Introductionmentioning
confidence: 99%
“…A wide number of dermatological conditions can be manifested orally [1]. Dermatoses have frequently been reported with different frequencies in the oral cavity [1]. One of the most important concerns about systemic lupus erythematosis (SLE) is the presence of oral lesions, which is one of its diagnostic criteria [2].…”
Section: Introductionmentioning
confidence: 99%